2014
DOI: 10.1007/s00125-014-3381-y
|View full text |Cite
|
Sign up to set email alerts
|

Rb and p107 are required for alpha cell survival, beta cell cycle control and glucagon-like peptide-1 action

Abstract: Aims/hypothesis Diabetes mellitus is characterised by beta cell loss and alpha cell expansion. Analogues of glucagonlike peptide-1 (GLP-1) are used therapeutically to antagonise these processes; thus, we hypothesised that the related cell cycle regulators retinoblastoma protein (Rb) and p107 were involved in GLP-1 action. Methods We used small interfering RNA and adenoviruses to manipulate Rb and p107 expression in insulinoma and alpha-TC cell lines. In vivo we examined pancreas-specific Rb knockout, whole-bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
(72 reference statements)
5
7
0
Order By: Relevance
“…Here, we report that E2F1 transcription factor, primarily known to control cell cycle progression (52), plays a key role in pancreatic b-cell function through the control of Glp-1 signaling, both in mice and human islets. Following previous studies demonstrating that E2F1-pRb pathway controls pancreatic b-cell mass (18,36,53,54) and function (17,55), we identify here a new role for this transcription factor linking this pathway to the druggable Glp-1 signaling. Indeed, we demonstrate that the specific loss of E2f1 expression in b cells leads to impaired oral glucose tolerance, both under chow and upon metabolic stress, associated to a loss of insulin secretion in response to glucose, despite normal Glp-1 circulating levels.…”
Section: Discussionsupporting
confidence: 60%
“…Here, we report that E2F1 transcription factor, primarily known to control cell cycle progression (52), plays a key role in pancreatic b-cell function through the control of Glp-1 signaling, both in mice and human islets. Following previous studies demonstrating that E2F1-pRb pathway controls pancreatic b-cell mass (18,36,53,54) and function (17,55), we identify here a new role for this transcription factor linking this pathway to the druggable Glp-1 signaling. Indeed, we demonstrate that the specific loss of E2f1 expression in b cells leads to impaired oral glucose tolerance, both under chow and upon metabolic stress, associated to a loss of insulin secretion in response to glucose, despite normal Glp-1 circulating levels.…”
Section: Discussionsupporting
confidence: 60%
“…Macrophages and granulocytes, which produce and secrete interleukin‐6, are found in islets of Goto–Kakizaki rats, which are often used as a non‐obese diabetic model. In contrast, glucagon‐like peptide‐1 accelerated β‐cell proliferation and reduced α‐cell proliferation by downregulating retinoblastoma protein. The decreased incretin effect associated with impaired glucose tolerance might also promote α‐cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, exendin-4, a GLP-1 agonist known to induce beta cell proliferation in mice, has been shown to decrease RB expression. Further study revealed that this decreased Rb expression is necessary for the beta cell proliferation stimulating effect of exendin-4 (Cai et al 2014). GLP-1 agonists increase miR-132 expression in beta cells (Shang et al 2015), suggesting that miR-132 plays a central role in the adaptive beta cell response to obesity and GLP-1.…”
Section: Discussionmentioning
confidence: 96%